PROGRAM MENINGKATKAN RASA KEPERCAYAAN DIRI PADA ANAK TARI DI RPTRA CIBUBUR BERSERI - Noverina, Angelica; Faura Irva Ikishima; Melzha Emrida Putri; Agustina (Jurnal Serina Abdimas, 2025)
Self-confidence is a fundamental aspect of children’s socio-emotional development, influencing their ability to interact, express themselves, and demonstrate their potential in various social contexts. This study aims to enhance the self-confidence of young dancers through an activity-based program conducted at the Child-Friendly Integrated Public Space (RPTRA) Cibubur Berseri as part of the Merdeka Belajar – Kampus Merdeka (MBKM) Humanitarian Project. The program was designed using participatory and creative approaches and implemented in three stages: delivering psychoeducational materials on the importance of self-confidence and interpersonal skills, conducting competitive activities to stimulate courage and cooperation, and organizing a dance competition as a form of expression and self-actualization. A total of 25 children aged 7–12 years actively participated in this program. The evaluation employed a pre-test and post-test design using a Likert-scale instrument to measure aspects of self- expression, communication, and self-assurance. Data analysis using the paired sample t-test showed a significant increase in post-test scores (p < 0.05), indicating that the program effectively improved children’s self-confidence. Behavioral observations also revealed greater active participation, increased courage to perform, and more positive social interaction skills. These findings reinforce the importance of applying experiential learning approaches to support the growth of children’s self-confidence and social independence. The results are expected to serve as a reference for developing non-formal educational programs that emphasize character building, self-potential development, creativity, cooperation, and socio-emotional well-being in an inclusive, sustainable, and socially relevant learning environment. Rasa percaya diri merupakan aspek fundamental dalam perkembangan sosial-emosional anak, yang memengaruhi kemampuan berinteraksi, berekspresi, dan menunjukkan potensi diri di berbagai konteks sosial. Penelitian ini bertujuan untuk meningkatkan rasa percaya diri anak-anak tari melalui program berbasis kegiatan yang dilaksanakan di Ruang Publik Terpadu Ramah Anak (RPTRA) Cibubur Berseri dalam kerangka Merdeka Belajar – Kampus Merdeka (MBKM) Proyek Kemanusiaan. Program ini dirancang dengan pendekatan partisipatif dan kreatif melalui tiga tahap kegiatan, yaitu penyampaian materi psikoedukatif tentang pentingnya rasa percaya diri dan keterampilan interpersonal, pelaksanaan kegiatan kompetitif untuk menstimulasi keberanian serta kerja sama, dan pelaksanaan lomba tari sebagai bentuk ekspresi serta aktualisasi diri. Sebanyak 25 anak berusia 7–12 tahun berpartisipasi aktif dalam kegiatan ini. Evaluasi dilakukan menggunakan desain pre-test dan post-test dengan instrumen skala Likert untuk mengukur aspek ekspresi diri, komunikasi, dan keyakinan diri. Analisis data menggunakan uji paired sample t-test menunjukkan adanya peningkatan signifikan pada skor post-test (p < 0,05), yang mengindikasikan bahwa program efektif dalam meningkatkan rasa percaya diri anak. Selain itu, hasil observasi perilaku memperlihatkan peningkatan partisipasi aktif, keberanian tampil, serta kemampuan berinteraksi sosial secara lebih positif. Temuan ini memperkuat pentingnya penerapan pendekatan pembelajaran berbasis pengalaman dalam mendukung tumbuhnya kepercayaan diri dan kemandirian sosial anak. Hasil penelitian diharapkan menjadi referensi bagi pengembangan program pendidikan nonformal yang berfokus pada pembentukan karakter, penguatan potensi diri, kreativitas, kerja sama, serta kesejahteraan sosial-emosional anak di masa depan yang berkelanjutan, inklusif, dan relevan dengan kebutuhan masyarakat..